REAPROVEITAMENTO DE RESÍDUO AGROINSDUSTRIAL COMO BIOTEMPLATE NA SÍNTESE DE NANOPARTÍCULAS - BRITO, Guilherme Nascimento; FEGADOLI, Ively Maria Pereira; RODRIGUES, Daniela Cristina Manfroi; NJOS, Ademir (ANAIS DO ENIC, 2024)
-